2019
DOI: 10.1002/cplu.201900435
|View full text |Cite
|
Sign up to set email alerts
|

Lyotropic Liquid Crystalline Mesophases Made of Salt‐Acid‐Surfactant Systems for the Synthesis of Novel Mesoporous Lithium Metal Phosphates

Abstract: Mesoporous lithium metal phosphates are an important class of materials for the development of lithium ion batteries. However, there is a limited success in producing mesoporous lithium metal phosphates in the literature. Here, a lyotropic liquid crystalline (LLC) templating method was employed to synthesize the first examples of LiMPO4 (LMP) of Mn(II), Co(II), and Ni(II). A homogeneous aqueous solution of lithium and transition metal nitrate salts, phosphoric acid (PA), and surfactant (P123) can be spin coate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 50 publications
0
16
0
1
Order By: Relevance
“…Mesoporous and nanoscaled metal oxides, metal sulfides, carbon, metal–organic frameworks, and phosphates are important materials in the production and storage of clean energy. Especially, mesoporous spinel oxides have been widely investigated for water oxidation electrocatalysis. Transition-metal cobaltites (MCo 2 O 4 ) are employed as efficient electrocatalysts for water oxidation and as electrodes in supercapacitors and batteries; therefore, many strategies have been developed to synthesize these materials. , Most methods produce powder samples that require further fabrication steps and special chemicals to build into electrodes. Designing synthetic strategies that involve one-pot, single-step film fabrication would help to enable the development of these electrodes for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Mesoporous and nanoscaled metal oxides, metal sulfides, carbon, metal–organic frameworks, and phosphates are important materials in the production and storage of clean energy. Especially, mesoporous spinel oxides have been widely investigated for water oxidation electrocatalysis. Transition-metal cobaltites (MCo 2 O 4 ) are employed as efficient electrocatalysts for water oxidation and as electrodes in supercapacitors and batteries; therefore, many strategies have been developed to synthesize these materials. , Most methods produce powder samples that require further fabrication steps and special chemicals to build into electrodes. Designing synthetic strategies that involve one-pot, single-step film fabrication would help to enable the development of these electrodes for practical use.…”
Section: Introductionmentioning
confidence: 99%
“…Было установлено, что жидкокристаллическая мезофаза чувствительна к типу аниона в применяемых солях и ионной силе среды. В настоящее время эти исследования продолжаются; металлсодержащие лиотропные ЖК успешно используются в качестве темплатов для получения мезопористых солей ванадия, лития и других элементов [108][109][110]. Применение в качестве лигандов переходных металлов находят и катионные ПАВ.…”
Section: металломицеллярные системы на основе пав с глюкаминовым фрагunclassified
“…We have shown that lithium nitrate-transition metal nitrateÀ phosphoric acid-surfactant mes-ophases can be used to synthesize mesoporous LMPs. [27] The use of LiH 2 PO 4 , as a lithium and phosphate source in the synthesis of mesoporous LMPs, can be beneficial as it eliminates some of the nitrates that require high temperatures to remove from the LMPs. Therefore, it is worth investigating the phase behaviors and stability issues of the LiÀ EOÀ X mesophases towards the above two goals.…”
Section: Introductionmentioning
confidence: 99%
“…However, a stable Li−EO−X mesophase will be very beneficial for both gel‐electrolytes (as both lithium and proton conductors) and for the synthesis of mesoporous lithium metal phosphates (LMPs), [27] which are important in lithium‐ion batteries. We have shown that lithium nitrate‐transition metal nitrate−phosphoric acid‐surfactant mesophases can be used to synthesize mesoporous LMPs [27] . The use of LiH 2 PO 4 , as a lithium and phosphate source in the synthesis of mesoporous LMPs, can be beneficial as it eliminates some of the nitrates that require high temperatures to remove from the LMPs.…”
Section: Introductionmentioning
confidence: 99%